Analisis Hukum dan Etika dalam Transaksi Ijarah pada Operasional Perbankan Syariah - Mujib, Muhammad Abdul (Journal of Islamic Finance and Syariah Banking, 2023)
This research aims to explain the law and ethics of ijarah transactions in Sharia banking operations. This research uses a qualitative descriptive method, a data collection technique used by libraries (library research). The results of this research show that ijarah transactions are characterized by a transfer of profits. Basically, the principle of ijarah is the same as the principle of buying and selling. However, the difference is that the object of the transaction is goods, while the object of business in ijarah is services. And the law on ijarah transactions is permitted, because the services being transacted are halal services, the most important thing is that ijarah transactions must comply with clear provisions and rules that can prevent disputes between the two parties to the transaction. This only happens to Sharia banking which has its own characteristics that are different from conventional banks. The essence of sharia banking is not only seen from the absence of a usury system in all transactions but is based on Sharia principles, namely the principle of profit sharing.